Synthesis and characterization of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages - Pal, R. R.; Patil, P. S.; Salunkhe, M. M.; Maldar, Noormahamad N.; Wadgaonkar, P. P. (Polymer International, 2005)
A series of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages was synthesized from two new diacids, namely 2,4-bis-(4-carboxyphenoxy)-6-thiophenoxy-s-triazine and 2,4-bis-(3-carboxyphenoxy)-6-thiophenoxy-s-triazine, and commercially available aromatic diamines by using Yamazaki's phosphorylation reaction. The polyamides were obtained in good yields and were characterized by solubility tests, viscosity measurements, FTIR, H-1 and C-13 NMR spectroscopy, X-ray diffraction studies and thermogravimetric analysis. The polyamides were found to have inherent viscosities in the range of 0.35 to 0.56 dl g(-1) in N,N-dimethylacetamide (DMAc) at 30 +/- 0.1 degreesC. All the polyamides were readily soluble in solvents such as DMAc, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF) and m-cresol. Thermogravimetric analysis of the polyamides indicated no weight loss below 345 degreesC under a nitrogen atmosphere. (C) 2004 Society of Chemical Industry.
Keywords: 2; 4-bis-(3/4-carboxyphenoxy)-6-thiophenoxy-s-triazine; direct polycondensation; polyamide; s-triazine ring

Synthesis of aromatic poly(amide-imide)s from novel diimide-diacid (DIDA) containing sulphone and bulky pendant groups by direct polycondensation with various diamines - Patil, Prashant S.; Pal, Ravindra R.; Salunkhe, Manikrao M.; Maldar, Noormahamad N.; Wadgaonkar, Prakash P. (European Polymer Journal, 2007)
A novel diimide-diacid (DIDA) monomer, 4-{4-[(4-methyl phenyl) sulphonyl]}-1,3-bis-trimellitoimido benzene containing sulphone and bulky pendant groups was successfully synthesized and used to synthesize a series of wholly aromatic poly(amide-imide)s (PAIs) by direct polycondensation method. The direct polycondensation of newly synthesized DIDA with different diamines was carried Out via Yamazaki's phosphorylation method using triphenyl phosphite and pyridine system. The resulting poly(amide-imide)s were obtained in quantitative yields with inherent viscosities 0.36-0.47 dl/g in DMAc at 30 +/- 0.1 degrees C. The poly(amide-imide)s were amorphous and were readily soluble in various solvents such as N-methyl-2-pyrrolidinone (NMP), NN-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), dimethylsulfoxide (DMSO), and pyridine. Tough and flexible films were obtained by casting their DMAc solution. According to thermogravimetric analysis, the polymers were fairly stable up to temperature around 396 degrees C, and 10% weight losses in the temperature range of 476-511 degrees C that showed good thermal stabilities of these polymers. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: direct polycondensation; poly(amide-imide)s; sulphone and bulky pendant groups; thermally stable polymers